Fuzzy multi-objective mixed integer linear programming based secondary voltage control - Zhihao Yun; Yutian Liu; Hong Mu; Xiaohong Ma (7th IET International Conference on Advances in Power System Control, Operation and Management (APSCOM 2006), 2006)
The hierarchical voltage control has been utilized and proved as an effective method in some power systems. The secondary voltage control provides voltage support to an area of the transmission network. There are several control objectives should be considered in the secondary voltage control and some objectives and constraints have accepted tolerance dealt with by fuzzification. Therefore, a secondary voltage control method based on fuzzy multi-objective mixed integer linear programming is proposed in this paper. To incorporate tolerance of the objectives, the fuzzy goals are adopted, and the fuzzy logic method is proposed in this paper for ranking the priority of each objective and defining the constraints of adjusting number of the shunt capacitor/reactor and OLTC transformer which are controlled in a coordinated way in a control zone. Then this problem can be solved by fuzzy goal programming and some simulation results of secondary voltage control at Zouxian power plant demonstrated the feasibility of the method. (6 pages)